Limits of prenatal care coordination for improving birth outcomes among Medicaid participants - Cross-Barnet, Caitlin; Benatar, Sarah; Courtot, Brigette; Hill, Ian (Elsevier, 2022)
Maternity Care Homes (MCHs) intend to address clinical and psychosocial needs for perinatal patients and are commonly implemented for Medicaid beneficiaries. Rigorous evidence supporting MCHs' effectiveness for improving birth outcomes is thin, but most studies consider only clinical and demographic factors from administrative data. To assess birth outcomes with controls for psychosocial variables known to affect them, this paper considers quantitative participant-level data from the Strong Start for Mothers and Newborns prenatal care initiative, with qualitative case study data to further contextualize results. From 2013 to 2017, Strong Start served over 45,000 Medicaid beneficiaries in 32 states, D.C., and Puerto Rico though MCHs, group prenatal care, or freestanding birth centers. Participant data included risks screens for food insecurity, depression, anxiety, pregnancy intention, and intimate partner violence, in addition to clinical and demographic information. After clinical, demographic and psychosocial risks were controlled in a regression model, Strong Start birth center participants showed significantly lower rates of preterm birth, low birthweight, and cesarean section relative to MCH participants (p < .01). In group prenatal care, White participants showed lower rates of preterm birth (p < .01) and Black participants showed lower rates of low birthweight (p < .05) relative to MCH participants. Strong Start participants reported appreciation for MCH care managers' support, but community and clinical referrals often had long waiting lists or were inaccessible. Transformative care models focusing on provider continuity, relationship building, and patient activation may offer more promise for improving birth outcomes than supplementing medical models with care management and other resources.
Keywords: Cesarean rates; Care coordination; Equity; Preterm birth; Prenatal care